CHL1 expression differentiates Hürthle cell carcinoma from benign Hürthle cell nodules. Issue 6 (12th October 2018) - Li, Wei; Xia, Shujun; Aronova, Anna; Min, Irene M.; Verma, Akanksha; Scognamiglio, Theresa; Gray, Katherine D.; Ullmann, Timothy M.; Liang, Heng; Moore, Maureen D.; Elemento, Olivier; Zarnegar, Rasa; et al.
Abstract : Background and Objectives: Hürthle cell carcinoma (HCC) is an unusual and relatively rare type of differentiated thyroid cancer. Currently, cytologic analysis of fine‐needle aspiration biopsy is limited in distinguishing benign Hürthle cell neoplasms from malignant ones. The aim of this study was to determine whether differences in the expression of specific genes could differentiate HCC from benign Hürthle cell nodules by evaluating differential gene expression in Hürthle cell disease. Methods: Eighteen benign Hürthle cell nodules and seven HCC samples were analyzed by whole‐transcriptome sequencing. Bioinformatics analysis was carried out to identify candidate differentially expressed genes. Expression of these candidate genes was re‐examined by quantitative real‐time polymerase chain reaction (qRT‐PCR). Protein expression was quantified by immunohistochemistry. Results: Close homolog of L1 (CHL1) was identified as overexpressed in HCC. CHL1 was found to have greater than 15‐fold higher expression in fragments per kilobase million in HCC compared with benign Hurthle cell tumors. This was confirmed by qRT‐PCR. Moreover, the immunoreactivity score of the CHL1 protein was significantly higher in HCC compared with benign Hürthle cell nodules. Conclusions: CHL1 expression may represent a novel and useful prognostic biomarker to distinguish HCC from benign Hürthle cell disease.